ANALISIS KEBERLANJUTAN PEMBIBITAN SAPI POTONG PADA BPTU-HPT PADANG MENGATAS - Pinta Aftaprilia Rizki Ananda; Rita Nurmalina; Burhanuddin Burhanuddin; Harry Suhada (Jurnal Agribisnis Indonesia, 2021)
Beef cattle breeding is one of the most important production factors and the quality of beef cattle breeds can affect the level of beef production. The increase in demand for beef is not followed by an increase in population and national beef productivity. The government is trying to fulfill the needs of domestic cattle breeds by establishing a Technical Implementation Unit for beef cattle breeding in various regions, one of which is Padang Mengatas BPTU-HPT. The most widely breed cattle breeders is local cattle, namely pesisir’s cattle. Therefore, in this study, it is needed to analyze the sustainability of pesisir’s cattle breeds in BPTU-HPT Padang Mengatas. Data collection using primary data was obtained by interviewing the respondents with the stakeholders. A secondary data was conducted using literature review from documents from various related institutional sources. Datawas processed using the Rap-Local Beef Cattle Breeding ordination technique through the mutidimensional scaling (MDS) method for sustainability analysis. Our results indicated the sustainability status of pesisir’s cattle breeding in multidimensional is quite sustainable, because the index value is at an interval of 50.01 until 75.00 with a value of 72.89 in the economic dimension, 67.96 in the ecological dimension, 67.78 in the social dimension, and 56.04 in the technological dimension.